2012
DOI: 10.1002/glia.22327
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 4 participates in the myelin disruptions associated with chronic alcohol abuse

Abstract: Alcohol abuse and alcoholism can cause brain damage, loss of white matter, myelin fiber disruption, and even neuronal injury. The underlying mechanisms of these alterations remain elusive. We have shown that chronic ethanol intake, by activating glial toll-like receptor 4 (TLR4) receptors, triggers the production of inflammatory mediators and can cause brain damage. Because neuroinflammation may be associated with demyelination and neuronal damage, we evaluate whether the ethanol-induced TLR4-dependent proinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 54 publications
7
86
1
4
Order By: Relevance
“…Dysregulated ubiquitination contributes to the development of Alzheimer's disease and other neurodegenerative disorders [for review, see (8)], and is associated with demyelination and white matter degeneration (123). Myelin degradation has been associated with ethanol abuse (2,28,68), but to our knowledge males and females have not been examined separately. Though complex, TNF production has been associated with enhanced demyelination (66), while Tgfb1 expression reduces demyelination (33).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated ubiquitination contributes to the development of Alzheimer's disease and other neurodegenerative disorders [for review, see (8)], and is associated with demyelination and white matter degeneration (123). Myelin degradation has been associated with ethanol abuse (2,28,68), but to our knowledge males and females have not been examined separately. Though complex, TNF production has been associated with enhanced demyelination (66), while Tgfb1 expression reduces demyelination (33).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 receptors are constitutively expressed on microglia, making microglia a key component of drug-induced neuroimmune activation (Alfonso-Loeches & Guerri, 2011; Schwarz & Bilbo, 2013). More recent studies by Guerri’s laboratory have found that TLR4 receptors are integral to ethanol-induced dopamine release (Alfonso-Loeches & Guerri, 2011), damage to white matter (Alfonso-Loeches et al, 2012), and other pathologies associated with chronic ethanol-induced changes in brain (Pascual et al, 2011). In culture, ethanol treatment increases innate immune gene expression in a time-dependent fashion mimicking responses to LPS or IL-1β administration, although ethanol induces a much smaller response (Crews et al, 2013).…”
Section: Alcohol Neuroimmune Signaling and Neurodegenerationmentioning
confidence: 99%
“…Alcohol also has a genotoxic effect [16]. In the case of chronic alcohol abuse, white matter decreases as a result of inhibition of the remyelination and apoptosis of glial cells proportional to the quantity of alcohol consumed [17]. In comparative studies of alcohol addicted patients with and without thiamine deficiency, atrophy was more pronounced both regionally and globally in vitamin-deficient patients.…”
Section: Atrophymentioning
confidence: 99%